Sistem Informasi Administrasi Negeri Ameth Berbasis Web - Puturuhu, Victor; Manuputty, Evandro Adolf Willem; Haurissa, Marceau A. F. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Negeri Amet is one of the villages in Central Maluku Regency in Nusa Laut District. Service to the community is the main task that must be carried out by the staff of the Ameth government. In carrying out community service activities, good human resources are needed by preparing the staff of the Ameth Government to help people in need. People usually come to the office of the Ameth government to take care of population administration. The Ameth Country Management Information System was created to answer the problems that exist in Ameth Country related to population administration. In addition, this system is used to view the Ameth Country Citizen Profile Data. The purpose of this study is to conduct an analysis to produce an integrated state administration information system that can be accessed in real time. The study used to support this study uses the Waterfall model with stages such as: 1. System planning, planning related to resource requirements that will be used in the study 2. System analysis is a stage regarding the proposed framework of the system to be built 3. System design, talking about the design of the system to be built 4. System implementation is a stage where the system has been created and is ready to run 5. System maintenance talks about how to maintain applications that have been built, so as to produce a reliable State Ameth Management Information System that can support the service process for the people of the state of Ameth. Keywords: State Management Information System